The Effect of Safety Shipping at Sea on Ship Traffic Safety Mediated Organizational Commitment (Survey on Tanjung Priok Marine and Coastal Guard Units in 2020) - Yosi Pahala; D.A. Lasse; Datep Purwa Saputra; Zaenal Abidin; Leonard Immanuel (Budapest International Research and Critics University, 2022)
The ultimate ambition at this research was to conclude the direct and indirect influence of the influence of shipping safety at sea on the safety of ship traffic mediated by organizational commitment (survey on the Tanjung Priok Marine and Coastal Guard Unit in 2020). The design usage of the particular research was not only associated and as the complimentary work under the survey method but also related to the population which was the captain of the Tanjung Priok Marine and Coast Guard Unit. By using the sampling technique, this research has its purposive sampling with a total sample of 66 respondents and by implementing the data collection technique, quantitative questionnaire has been passed the trial and error for its validity and reliability. Under the Research Methodology theorem, this research is implementing the path analysis method with Smart Partial Least Square software ver. 3. The conclusion has indicate that shipping safety at sea has a direct effect on organizational commitment.